Expression of FIBCD1 by intestinal epithelial cells alleviates inflammation-driven tumorigenesis in a mouse model of colorectal cancer - Shahgoli, Vahid Khaze; Dubik, Magdalena; Pilecki, Bartosz; Skallerup, Sofie; Schmidt, Sandra Gaedt; Detlefsen, Sönke; Sorensen, Grith L.; Holmskov, Uffe; Baradaran, Behzad; Moeller, Jesper B. (Frontiers in Oncology, 2023)
Background Colorectal cancer (CRC) ranks as the third most prevalent cancer globally, highlighting the pressing need to address its development. Inflammation plays a crucial role in augmenting the risk of CRC and actively contributes to all stages of tumorigenesis. Consequently, targeting early inflammatory responses in the intestinal tract to restore homeostasis holds significant potential for preventing and treating CRC. Fibrinogen C domain-containing 1 (FIBCD1), a chitin-binding transmembrane protein predominantly found on human intestinal epithelial cells (IECs), has garnered attention in previous research for its ability to effectively suppress inflammatory responses and promote tissue homeostasis at mucosal barriers. Methods In this study, we investigated the role of FIBCD1 in CRC development using transgenic mice that mimic human expression of FIBCD1 at the intestinal mucosal barrier. To model aspects of CRC, we employed the azoxymethane/dextran sodium sulfate (AOM/DSS) mouse model. Additionally, we examined the expression pattern of FIBCD1 in surgical specimens obtained from human CRC patients by immunohistochemical methods. By accessing public data repositories, we further evaluated FIBCD1 expression in colon adenocarcinoma and explored survival outcomes associated with FIBCD1 expression. Results Here, we demonstrate that FIBCD1 substantially impacts CRC development by significantly reducing intestinal inflammation and suppressing colorectal tumorigenesis in mice. Furthermore, we identify a soluble variant of FIBCD1 that is significantly increased in feces during acute inflammation. Finally, we demonstrate increased expression of FIBCD1 by immunohistochemistry in human CRC specimens at more developed tumor stages. These results are further supported by bioinformatic analyses of publicly available repositories, indicating increased FIBCD1 expression in tumor tissues, where higher expression is associated with unfavorable prognosis. Conclusion Collectively, these findings suggest that FIBCD1 influences early inflammatory responses in the AOM/DSS model, leading to a reduction in tumor size and burden. The increased expression of FIBCD1 in human CRC samples raises intriguing questions regarding its role in CRC, positioning it as a compelling candidate and novel molecular target for future research.